A formação do professor de artes na rede estadual de ensino de Tocantinópolis - TO: um estudo exploratório - Oliveira, Sabrina Borges de (Universidade Federal do Tocantins, 2019)
The research sought to problematize the training of teachers in the discipline of Art in the state educational network of that city, with the purpose of analyzing the profile of the art teachers who work in the state network of the city of Tocantinópolis-TO. As methodological procedures, the research is characterized as being of qualitative approach, bibliographical and documentary characteristic. As a data collection instrument, we used a semi-structured questionnaire applied to these teachers. Among the results found, most of the teachers working in this discipline in the schools studied do not have training in the arts area to teach students content related to artistic languages, thus impairing the academic formation of students regarding teaching and learning in the arts, even the majority reporting that art is important and needs to be on the school curriculum. It was also observed, from the reports of the teachers surveyed that the majority, besides not having the training in the area, works in the arts discipline for a short time in comparison with their experiences of teachers in basic education, since the majority reported that is formed in other areas of knowledge, such as Pedagogy and use, in turn, the discipline of arts to complement workload in schools that work, which reinforces the thesis that this area, in addition to not being valued in the school curriculum, makes it clear that any teacher, from any area, can minister it. These results make evident the lack of initial and continuing arts courses in the region. Art is an area of knowledge and important for the full education of the student as well as for his aesthetic perception. With this, it is necessary that the teacher’s present training in this area as highlighted in the official documents as in PCNs, LDB 9.394 / 96 among others. You can not just stay in theory and in practice be totally different. In addition, there must also be a consonance between the state documents (Directives, state and DRE regiments) with the national ones (PCNs, LDB, Law No. 13.278/2016), regarding the teaching of art, because to teach in that area, must be trained in it and have more initial and continuing training in visual arts, theater, dance and music, so that they can meet the great demand of professionals of this area in Tocantins, especially in the region analyzed. We hope that the research carried out may contribute to other studies with this theme, by broadening the discussions developed in this monograph on the formation of the art teacher in Tocantinópolis-TO, and that it is important to understand that a formation in the area of art is necessary, since is important to develop the creative, aesthetic and formative potential of the learner.